Sentiment Discourse: An Intersection of News Text and Comments on Social Media - I Gusti Ngurah Parthama; I Wayan Pastika; I Made Netra; I Nyoman Aryawibawa (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study examines the intersection of sentiment discourse in news texts and user comments on Facebook Detikcom, focusing on government policies during the Covid-19 pandemic. The research explores institutional discourse in news articles that align with government narratives, while user comments reflect a spectrum of responses, from support to opposition. Using qualitative content analysis, this study applies critical discourse analysis (CDA) and sentiment analysis to examine linguistic strategies, ideological framing, and sentiment polarity. The data were taken from news texts and the comment section on Facebook Detikcom, collected through documentation and following several stages of observation, careful reading, selection, and classification. The findings show that social media transforms news consumption into a participatory discourse. This indicates that traditional narratives are challenged and reinterpreted by users. Sentiment clustering and engagement metrics further shape the visibility and influence of competing ideologies. This study contributes to digital discourse research by demonstrating that sentiment functions as an ideological tool in crisis communication. The analysis also highlights the evolving role of social media in public discourse and emphasizes the need for critical engagement with online news narratives and user-generated content.